Pyrometamorphism - Grapes, Rodney; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Pyrometamorphism is a type of contact metamorphism (sanidinite facies) involving very high temperatures that may cause fusion in suitable lithologies at very low pressures. The high temperatures are attained by flow of mafic magma through conduits, by way of spontaneous combustion of coal, carbonaceous sediments, oil and gas, and through the action of lightning strikes. Temperature gradients are typically extreme, varying by several hundred degrees over a few metres or even centimetres. Relatively short periods of heating and cooling create an environment dominated by metastable melting and rapid mineral reaction rates driven by significant temperature overstepping of equilibrium conditions. This results in the formation of a large variety of minerals, many of which are metastable and are only found in pyrometamorphic rocks. The book is aimed for the specialist but also for students and researchers looking for an introduction into pyrometamorphism.
Introduction -- Thermal Regimes and Effects -- Quartzofeldspathic Rocks -- Calc-Silicates and Evaporites -- Mafic Rock -- Anthropogenic Pyrometamorphism -- Mineral Breakdown Reactions. Chapter 1 Additional terms and discussion from IUGS Subcommission on Systematics of Metamorphic Rocks (Contact metamorphism) Chapter 2 Further details on thermal regimes of combustion metamorphism and lightning strike pyrometamorphism + 1 diagram (various sources) Chapter 3 Additional example of pyrometamorphism of granitic rock by basalt + 1 diagram Additional examples of combustion metamorphism of quartzofeldpathic rocks + siderite from Siberia, New Zealand, Ellesmere Island (Canada) + 3 diagrams Additional material on paralava compositions Chapter 4 Additional pyrometamorphic examples of marl rocks from Israel + 3 diagrams Additional information on paralava compositions + 2 diagrams Example of lightning strike pyrometamorphism of carbonate rock Chapter 5 Additional example of pyrometamorphic recrystallization of basalt xenoliths + 1 diagram Additional example of lightning strike fusion of basaltic rock Chapter 6 Additional examples of pyrometamorphic minerals in carbonate mudstone bricks/kiln artifacts New section on biomass pyrometamorphism: 'tree stones' and slag/clinker as a result of forest fires, burning dung heaps, plant waste, straw, gorse, etc., + 2-4 diagrams; industrial biomass incineration products, wood ash + 1 diagram Additional examples of slag formation + 1 diagram Additional example of artificial fulgurite from Portugal + 1 diagram Experimental fulgurite formation + 1 diagram Chapter 7 Additional photo of hornblende breakdown Additional information on garnet breakdown + 2 diagrams Additional information on staurolite breakdown + 1 diagram.
Keywords: Mineralogy; Mineral resources; Geochemistry; Mineralogy; Mineral Resources; Geochemistry